Effects of body mass index and extracurricular sports activities on physical fitness in school-aged children - Aniśko, Bartosz; Bernatowicz, Kacper; Wójcik, Małgorzata (Frontiers in Public Health, 2025)
BackgroundWe are seeing a steady decline in children’s physical fitness. Along with overweight and obesity, low physical fitness is one of the most serious disorders in child development. One solution to these problems is additional physical activity. It was investigated whether reduced physical fitness is associated with an increased body mass index and whether children who participate in extra-curricular sports activities have better physical fitness.MethodsThe study involved 201 children (101 girls, 100 boys) aged 10 ± 2 (grades 1–8 of the primary school). Half of the participants reported participating in extra-curricular sports activities, while half did not participate in any sports activities. The children were assessed for body mass index, grip strength, balance, strength, speed and reaction time.ResultsSignificant differences in fitness test results were observed between active and inactive students. Significant differences were also found between students with different body mass index. The 4 months of schooling had a positive effect on most of the fitness characteristics assessed. Grip strength appeared to be a determinant of the other fitness scores.ConclusionThe hypotheses that both additional physical activity and BMI will influence children’s fitness, and that 4 months of schooling will have a positive effect on improving students’ fitness, were confirmed. Hand-grip strength was found to be a determinant of better performance in almost all other fitness tests.